Comparative Evaluation of Octa Shot Versus Quad Shot Palliative Radiotherapy for Advanced Head and Neck Cancer Patients - Jakhar, Shankar Lal; Dhaka, Shankar Singh; Dhaka, Saroj; Kumar, Rajesh; Singh, Guman; Sharma, Neeti; Kumar, Dr H. S. (Asian Pacific Journal of Cancer Care, 2023)
Background and Objective: The majority of patients with Head and Neck Squamous Cell Cancer in India present at advanced stages, making them unsuitable candidates for multimodality treatment due to loco-regionally advanced disease and poor performance status. Hypofractionated regimens have been used for palliation of advanced head and neck cancers. The purpose of this study was to compare the acute and late toxicity and overall response of octa shot and quad shot radiation therapy as a palliative regimen in locally advanced head and neck cancers. Materials and Methods: This hospital-based prospective, randomized study was conducted with 50 patients with advanced Squamous cell carcinoma of the head and neck, with 25 patients allocated to each treatment arm. Octa shot involved administering two fractions (3.5Gy/#) per day, six hours apart, for four consecutive days. Quad shot involved administering two fractions (3.5Gy/#) per day, six hours apart, for two consecutive days, repeated for one more cycle with a two-week interval. Acute toxicities were monitored at day 15 and 30, and late toxicities were assessed at 3 and 6 months after the treatment initiation. Results: Octa shot demonstrated slightly better loco-regional control, although the difference was not statistically significant. Octa shot resulted in more grade 2 skin and mucosal reactions compared to Quad shot. Symptomatic relief, subjective regression, and improved quality of life were better in the Octa shot group compared to the Quad shot group. Conclusion: Based on the findings of this study, "octa shot" can be an effective palliative radiotherapy regimen with greater yet manageable toxicity compared to the Quad shot regimen. This approach not only can balance the economic burden, treatment time, and machine load, but also can aid in selecting patients for further dose escalation based on treatment response and symptomatic relief. However, further trials with longer follow-up periods and larger sample sizes are required to provide stronger evidence.